Response of the gullet to gastric reflux in patients with hiatus hernia and oesophagitis - Woodward, D. A. K. (1970)
The variability of reflux symptoms in patients with hiatus hernia is well known, and a poor correlation between the symptoms of oesophagitis and appearances at oesophagoscopy has been noted. A study has been made of the relationship between four variables. These are the acid reflux occurring in the oesophagus, the peristaltic clearance, the oesophagitis present and the symptoms from which the patients are suffering. Symptoms were found only in patients with oesophageal pH levels below 4. However, such acid levels could occur in the absence of significant symptoms and there was a poor correlation between symptoms and various levels of pH below this. Poor motor function in the oesophagus was associated with poor clearance of acid from it. Patients with poor clearance show a greater tendency to have oesophagitis, but, despite this correlation, in the group as a whole, there was no clear relationship between the results of the tests and the severity of symptoms.